Self-reactivities to the non-erythroid alpha spectrin correlate with cerebral malaria in Gabonese children - Guiyedi, V. (2011)
Hypergammaglobulinemia and polyclonal B-cell activation commonly occur in Plasmodium sp. infections. Some of the antibodies produced recognize self-components and are correlated with disease severity in P. falciparum malaria. However, it is not known whether some self-reactive antibodies produced during P. falciparum infection contribute to the events leading to cerebral malaria (CM). We show here a correlation between self-antibody responses to a human brain protein and high levels of circulating TNF alpha (TNFα), with the manifestation of CM in Gabonese children